A framework for managing health research capacity strengthening consortia: addressing tensions and enhancing capacity outcomes. Issue 10 (3rd October 2022) - Tagoe, Nadia; Pulford, Justin; Kinyanjui, Sam; Molyneux, Sassy
Abstract : There has been a steady increase in health research capacity strengthening (HRCS) consortia and programmes. However, their structures and management practices and the effect on the capacity strengthening outcomes have been underexamined. We conducted a case study involving three HRCS consortia where we critically examined the consortia's decision-making processes, strategies for resolving management tensions and the potential implications for consortia outcomes. We conducted 44 in-depth interviews with a range of consortia members and employed the framework method to analyse the data. We assessed the extent to which consortia's management practices and strategies enabled or hindered research capacity strengthening using a capacity development lens. At the heart of consortium management is how tensions are navigated and the resolution strategies adopted. This study demonstrates that the management strategies adopted by consortia have capacity strengthening consequences. When deciding on tension management strategies, trade-offs often occur, sometimes to the detriment of capacity strengthening aims. When management strategies align with capacity development principles, consortium management processes become capacity strengthening mechanisms for participating individuals and institutions. Such alignment enhances programme effectiveness and value for money. Drawing on these findings, we propose an evidence-informed management framework that consortia leaders can use in practice to support decision-making to optimise research capacity gains. Considering the increasing investment in HRCS consortia, leveraging all consortium processes towards capacity strengthening will maximise the returns on investments made.